Remediation of chromium-contaminated soil in semi-arid areas by combined chemical reduction and stabilization. Issue 1 (31st December 2023) - Pei, Yiqing; Yang, Yiming; Chen, Lihua; Yang, Yipeng; Song, Lingyan
ABSTRACT: The indoor simulation remediation of chromium-contaminated soil in semi-arid areas with chemical reduction-stabilization method was conducted to study the effects of remediation agent types and dosage, water (mL)-soil (g) ratio and remediation time on reduction and stabilization efficiency of the chromium-contaminated soil. The results showed that FeSO4 was the most effective reduction agent for reduction of Cr(VI) in soil. The optimally combined chemical reduction-stabilization remediation conditions were 2.5 times theoretical reaction dosage FeSO4 and 8% of modified corn stover biochar (KBC), 50% of water-soil ratio, and 7 days remediation time. The total Cr and Cr(VI) leaching concentrations and Cr(VI) content in soil were reduced from 65.65 mg L-1, 61.98 mg L-1 and 1000.00 mg kg-1 without treatment to 0.114 mg L-1, 0.125 mg L-1 and 18.909 mg kg-1 after treatment, respectively. They were according with comprehensive wastewater discharge standards and construction land soil contamination risk control standards, respectively. Graphical abstract: uf0001